Docetaxel combined with oral etoposide as second-line treatment for advanced gastric carcinoma after failure of platinum- and fluoropyrimidine-based regimens - (:unkn) unknown (My University, 2010)
Background. Platinum, antracyline, and fluoropyrimidine combination chemotherapy has been widely used as a first-line treatment for advanced gastric cancer (AGC). In the present study, we determined the efficacy and the safety of docetaxel and oral etoposide as second-line combination chemotherapy after failure of commonly used combination regimens in AGC. Methods. Patients with histologically proven gastric cancer and measurable metastatic disease received docetaxel 75 mg/m2 as a 1-h intravenous infusion on day 1, and oral etoposide 50 mg/m2 once daily on days 1-5, every 3 weeks until disease progression or unacceptable toxicities. Results. Between June 2006 and September 2008, 32 patients, of median age 60 years (range 32-77 years) were included in the study. Overall response rate was 9.4% and 31.3% of patients achieved a stable disease. Median progression-free survival was 3 months (95% CI, 2.5-3.5). Median overall survival was 6 months (95% CI, 3.8-8.2) with 16.9% 1-year survival rate. Grade 3-4 toxicities included neutropenia (28.8%), febrile neutropenia (18.8%), thrombocytopenia (3.1%), nausea and vomiting (15.6%), diarrhea (9.4%), and mucositis (6.2%). Conclusion. Docetaxel and oral etoposide combination was moderately effective and safe in appropriately selected AGC patients after failure of platinum- and fluoropyrimidine-based combination regimens. © The Author(s), 2010.
Keywords: advanced gastric cancer; docetaxel; oral etoposide; second-line chemotherapy